Sustainable chemical and biological technologies for the production of enantiopure added-value molecules in biorefineries - Koutinas, Michalis; Parmaki, Stella; Ferreira, Frederico Castelo; Esteves, Teresa; Afonso, Carlos A.M. (My University, 2022)
A continuously growing interest has emerged over the years pertinent to the sustainable production of enantiomerically pure compounds for the food, agrochemical, fine chemicals, medical, and pharmaceutical industries. A variety of biological and chemical methods have been developed enabling the manufacture of enantiopure molecules through three main processes, comprising chiral synthesis, chiral pool, and racemic approaches. Biocatalytic technologies provide the opportunity for single enantiomers’ production exploiting the activity of common or enhanced enzymes (e.g., immobilized or engineered enzymes) and a range of fermentation methods, such as suspended, resting, or immobilized cells. The chemical production of enantiopure molecules can be accomplished through several methods, including asymmetric synthesis, diastereomeric recrystallization, and other alternative chiral resolution approaches, such as chromatography and enantioselective extraction. The current chapter presents current advances in the aforementioned approaches incorporating a critical evaluation that demonstrates the advantages and disadvantages of the biological and chemical methods reviewed. An illustrative example exhibiting the integrated production of the valuable enantiopure alkaloid D-(+)-sparteine from lupin bean processing industries wastewater is provided highlighting that the development of a biorefinery based on an industrial effluent constitutes an advanced sustainable approach for exploitation and treatment of the specific biowaste. Thus biorefineries developed using various biomass feedstocks, including lignocellulosic biomass, algae, and numerous waste-types, for production of enantiopure molecules, could substantially assist the effort of our community for circular bioeconomy advancement.
Keywords: Circular bioeconomy; biotransformations; diastereomers; catalysis; lupanine; sparteine